Verweise auf das Naturrecht in den Quellen des spätfeudalen ungarischen Privatrechts - P. Szabó, Béla (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
The aim of this revised text, presented as a lecture, is to answer the question, based on some known sources of early modern Hungarian private law, of the role that they assigned to references to natural law, natural equity and human nature in relation to certain private law institutions and rules. Based on the available sources, we have examined the significance of natural law arguments and ideas in early modern Hungary in two ways. On the one hand, as a preliminary question, we attempted to assess how the authors of early modern Hungarian legal literature approached the phenomenon of natural law. On the other hand, we looked for examples of the extent to which natural law has been used in the interpretation of legislation or possibly customary law, or as a secondary source of law in the case of shortcomings in the Hungarian legal system.